2019
DOI: 10.18632/oncotarget.27127
|View full text |Cite
|
Sign up to set email alerts
|

The p21 levels have the potential to be a monitoring marker for ribociclib in breast cancer

Abstract: Although cyclin-dependent kinase (CDK) 4/6 inhibitors have exhibited remarkable results for patients with estrogen receptor (ER)–positive breast cancer in clinical trials, the mechanism of CDK4/6 inhibitor resistance remains unclear. Thus, this study aimed to investigate the mechanism of CDK4/6 inhibitor resistance using two CDK4/6 inhibitor resistant breast cancer cell lines. We established CDK6 overexpressed cell lines (MCF7-C6) from MCF-7 cells using the stably transfected CDK6 expression vector. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…The released E 2 F transcription factors are then free to activate genes required for entry into the S phase and DNA replication [ 29 ]. In addition, a recent study reported that p21 levels were proportional to CDK4/6 inhibitor sensitivity and had the potential as a monitoring marker for ribociclib, an FDA-approved CDK4/6 inhibitor in late-stage breast cancer [ 30 ]. Notably, while our combination L30I40 significantly decreased CDK4/6 protein levels, we found that LUT targeted CDK4 only, but I3C preferred CDK6 exclusively, indicating that the synergistic inhibition of CD4/6 complex results from the combination of the inhibition of CDK4 by LUT and the suppression of CDK6 by I3C.…”
Section: Discussionmentioning
confidence: 99%
“…The released E 2 F transcription factors are then free to activate genes required for entry into the S phase and DNA replication [ 29 ]. In addition, a recent study reported that p21 levels were proportional to CDK4/6 inhibitor sensitivity and had the potential as a monitoring marker for ribociclib, an FDA-approved CDK4/6 inhibitor in late-stage breast cancer [ 30 ]. Notably, while our combination L30I40 significantly decreased CDK4/6 protein levels, we found that LUT targeted CDK4 only, but I3C preferred CDK6 exclusively, indicating that the synergistic inhibition of CD4/6 complex results from the combination of the inhibition of CDK4 by LUT and the suppression of CDK6 by I3C.…”
Section: Discussionmentioning
confidence: 99%
“…Other pathways that converge on CDK2 activation are changes to the CDK inhibitor proteins p21 Cip1/Waf1 and p27 Kip1 . This includes reduction of p21 Cip1/Waf1 (Iida et al 2019) and p27 Kip1 protein (Dean et al 2010). Increased expression of components of the cyclin D-CDK4/6 complexes such as CDK6, observed in (Yang et al 2017) and (Cornell et al 2019), could also increase CDK2 activity by engaging the p21 Cip1/Waf1 and p27 Kip1 inhibitory proteins and hence remove these inhibitors from CDK2 complexes (Tsubari et al 1999).…”
Section: :5mentioning
confidence: 99%
“…Based on the IC 50 s of PAL or ABE, the PAL-or ABE-resistant MCF-7 or KPL-1 cells were 3 to 6 times more cross-resistant to APL and ABE, respectively (Table 1). Cross-resistance among CDK4/6 inhibitors has been reported in both preclinical and clinical conditions [1,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%